2023
DOI: 10.1097/jsm.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Knowledge and Self-Reported Behaviors in Youth Rugby Players and Their Coaches: A Population-Wide Cross-Sectional Survey

Abstract: Objective: To investigate concussion knowledge and self-reported behaviors in Italian youth rugby players and their coaches. To investigate predictors of lower concussion knowledge and association between athletes' self-reported knowledge and behavior. Design: Cross-sectional, population-wide, survey study. Setting: All rugby clubs (n 5 52) of the Veneto region (Italy). Participants: Players and coaches of all under 15, 17 and 19 teams. Overall, 1719 athlete surveys (92.2% male; response rate, 71.1%) and 235 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Nevertheless, it has been shown that concussion is underdiagnosed because of low awareness, as demonstrated in a recent survey by Bazo et al on youth rugby players and their coaches [25]. A total of 1719 athletes and their coaches underwent a survey on knowledge about concussion.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been shown that concussion is underdiagnosed because of low awareness, as demonstrated in a recent survey by Bazo et al on youth rugby players and their coaches [25]. A total of 1719 athletes and their coaches underwent a survey on knowledge about concussion.…”
Section: Introductionmentioning
confidence: 99%